A comparative assessment of digital platform worker protection in the EU and ASEAN - Nur, Muhammad; Asmorojati, Anom Wahyu; Megawati, Megawati; Zuliyah, Siti; Isdiyanto, Ilham Yuli (Faculty of Law, University of Muhammadiyah Malang, 2023)
The rapid rise of the digital platform economy, connecting workers with employers, has transformed labor markets globally. This paper explores the regulatory approaches and policies safeguarding digital platform workers in the European Union (EU) and the Association of Southeast Asian Nations (ASEAN). While the EU demonstrates comprehensive labor protections, ASEAN's diverse economies present a tapestry of approaches. This analysis aims to provide valuable insights for policymakers, scholars, and stakeholders, shedding light on the evolving landscape of labor rights and the future of work in the digital age. This study uses a comparative research design to assess digital platform worker protection in the EU and ASEAN, highlighting differences, similarities, and emerging trends. It involves reviewing official documents and legislative texts from both regions to identify relevant policies and initiatives. This paper found that